Interleukin-6 stimulates gene expression of extracellular matrix components in bovine mesangial cells in culture - C. Zoja; A. Benigni; G. Piccinini; M. Figliuzzi; L. Longaretti; G. Remuzzi (Hindawi Limited, 1993)
The effect of interleukin-6 (IL-6) on gene expression of extracellular matrix components in bovine mesangial cells in culture has been investigated. IL-6 (100 U/ml) time dependently increased the steady state expression of mRNAs coding for α1 collagen III and fibronectin, both transcripts being 1.5- and 2.5-fold higher than basal level at 24 and 48 h, respectively. In contrast, IL-6 stimulated laminin mRNA expression only after 48 h incubation (2.5-fold upon basal level). These results suggest that IL-6 could favour glomerular matrix accumulation thus contributing to the development of glomerulosclerosis.